Intra‐ and interscan reproducibility using Fourier Analysis of STimulated Echoes (FAST) for the rapid and robust quantification of left ventricular twist. Issue 2 (30th April 2013) - Reyhan, Meral; Kim, Hyun J.; Brown, Matthew S.; Ennis, Daniel B.
<x xml:space="preserve">Abstract</x> Purpose To assess the intra‐ and interscan reproducibility of LV twist using FAST. Assessing the reproducibility of the measurement of new MRI biomarkers is an important part of validation. Fourier Analysis of STimulated Echoes (FAST) is a new MRI tissue tagging method that has recently been shown to compare favorably with conventional estimates of left ventricular (LV) twist from cardiac tagged images, but with significantly reduced user interaction time. Materials and Methods Healthy volunteers (N = 10) were scanned twice using FAST over 1 week. On day 1, two measurements of LV twist were collected for intrascan comparisons. Measurements for LV twist were again collected on day 8 for interscan assessment. LV short‐axis tagged images were acquired on a 3 Tesla (T) scanner to ensure detectability of tags during early and mid‐diastole. Peak LV twist is reported as mean ± SD. Reproducibility was assessed using the concordance correlation coefficient (CCC) and the repeatability coefficient (RC) (95% confidence interval [CI] range). Results Mean peak twist measurements were 13.4 ± 4.3° (day 1, scan 1), 13.6 ± 3.7° (day 1, scan 2), and 13.0 ± 2.7° (day 8). Bland‐Altman analysis resulted in intra‐ and interscan bias and 95% CI of −0.6° [−1.0°, 1.6°] and 1.4° (−1.0°, 3.0°), respectively. The Bland‐Altman RC for peak LV twist was 2.6° and 4.0° for intra‐ and interscan, respectively. The CCC was 0.9 and 0.6 for peak LV twist for intra‐ and interscan, respectively. Conclusion FAST is a semi‐automated method that provides a quick and quantitative assessment of LV systolic and diastolic twist that demonstrates high intrascan and moderate interscan reproducibility in preliminary studies. J. Magn. Reson. Imaging 2014;39:463–468. © 2013 Wiley Periodicals, Inc.